The Mediating Role of Job Satisfaction on the Effect of Transformational Leadership Style and Job Redesign on Organizational Commitment (Study on millennial employees of CV. Cahaya Metalindo) - B2041182015, YULIANTO (Equator Journal of Management and Entrepreneurship (EJME), 2021)
The purpose of this study was to examine the Mediating Role of Job Satisfaction (JS) on the Effect of Transformational Leadership Style (TLS) and Job Redesign (JR) on Organizational Commitment (OC). The method used is quantitative descriptive by using primary data and secondary data. Data collection techniques used interviews and questionnaires which were distributed to millennial employees who work at CV. Cahaya Metalindo. The sample of this research is 41 respondents of millennial employees. Data were analyzed using path analysis. The results showed that JR had no effect on JS and OC. TLS has a significant effect on JS and OC, and KK has a significant effect on OC Keywords: job redesign, transformational leadership style, job satisfaction, organizational commitment